THE EFFECTIVENESS OF REWRITING TECHNIQUE IN TEACHING DESCRIPTIVE TEXT - M. Hudri M. Hudri (Muhammadiyah University of Mataram, 2015)
The objective of this research was to observe the effectiveness of using paraphrasing technique in academic writing course at sixth semester of Muhammadiyah University of Mataram in Academic Year 2014/2015. The method used in this research was quantitative method namely quasi experimental design. The number of population of this research was 43 students. The writer took 43 students as the sample and divided into two classes namely class VI.A-VI.B which consist of 23 students as an experimental class that showed their English ability in paraphrasing technique and the second class B which consist of 20 students as a control class that showed their English in summarizing technique. The writer here employed t-test to obtain the data. The tests were pre-test and post-test. Pre-test was given in the first meeting; the aim was to know the student’s ability in paraphrasing technique. Then, post-test was given after students got treatment for 6 meetings for each class. After collecting and computing the data, the writer found that class A obtained higher score than class B. The mean score of class VI.A (experimental) was 9.95 while for class VI.B (control) was 6.2. The standard of deviation of the class was computed by using t-test. T-test was 5.95; the critical value was higher than t-table. The t-table was 2.021 at the confidence level of 0.05 (95%) and 2.704 at the confidence level of 0.01 (99%). The consultation of t-test to t-table were found that the t-test is 5.95t-table 2.021 (95%) and t-test 5.95 t-table 2.704 (99%). It means that the alternative hypothesis is accepted and null hypothesis is rejected. Therefore, the rewriting technique is effective in teaching descriptive text at the sixth semester of Muhammadiyah University of Mataram in academic year 2014/2015.